Malakoplakia of the gastrointestinal tract. Issue 664 (February 1981) - McClure, J.
Abstract : The clinical and pathological features of 3 cases of colonic malakoplakia are documented thereby bringing to 34 the total of recorded cases of malakoplakia involving the gastrointestinal tract. This is therefore the most common site of involvement outside the urogenital tract. A comprehensive review of the world literature on gastrointestinal malakoplakia has been made and the characteristic features of the condition have been delineated. There was a bimodal age incidence with a small cluster of cases occurring in childhood and associated with significant additional systemic disease. In the adult cases the average age was 57 years with a slight excess of males. The most commonly involved part of the gastrointestinal tract was the colon and colonic carcinoma was the most common associated disease.